2011
DOI: 10.1007/s12206-011-0201-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of laser assisted machining for silicon nitride ceramic according to machining parameters

Abstract: This paper describes the Laser Assisted Machining (LAM) that cuts and removes softened parts by locally heating the ceramic with laser. Silicon nitride ceramics can be machined with general machining tools as well, because YSiAlON, which was made up ceramics, is soften at about 1,000℃. In particular, the laser, which concentrates on highly dense energy, can locally heat materials and very effectively control the temperature of the heated part of specimen. Therefore, this paper intends to propose an efficient m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The force ratio such as feed force/cutting force is found to decrease on zirconia [28] and mullite [29] resulted at higher Tmr which indicates the evidence of significant softening of the work piece near the cutting zone and quasi-plastic deformation. It is observed that cutting speed has the most significant influence on surface roughness followed by feed rate and depth cut [30].…”
Section: Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The force ratio such as feed force/cutting force is found to decrease on zirconia [28] and mullite [29] resulted at higher Tmr which indicates the evidence of significant softening of the work piece near the cutting zone and quasi-plastic deformation. It is observed that cutting speed has the most significant influence on surface roughness followed by feed rate and depth cut [30].…”
Section: Ceramicsmentioning
confidence: 99%
“…The most common wear mechanism observed on laser assisted machining of zirconia with PCBN is abrasion, diffusion and adhesion [27]. But the abrasive and diffusive wear is not observed in LAM of silicon nitride [25,30] when compared to zirconia [27] due to low ductility and thermal diffusivity of zirconia. PCD is found to be not suitable for LAM on zirconia ceramics.…”
Section: Cutting Tool Materials Employed In Difficult To Machine Matementioning
confidence: 99%
“…However, their mechanical properties above 1100 °C will be significantly degraded [1], and their high temperature stability and safety cannot meet the aviation needs. SiC/SiC [2], C/C [3,4] and Si 3 N 4 [5] non-oxide composites possess higher melting point, but they are easily oxidized in the ultra-high temperature air environment, or at least their anti-oxidation ability is far from meeting the needs of aero engines, which leads to the sharp deterioration of their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the yield strength of the workpiece can be reduced by the preheating. [7][8][9][10] The method leads to about a 60-80% reduction in the processing cost. 8,11 The LAM process facilitates the more efficient machining of nickel-based superalloys, through for example, decreasing the cutting force and tool wear, reducing the occurrence of chattering and of catastrophic tool failure, and increasing the material removal rate (MRR).…”
Section: Introductionmentioning
confidence: 99%